Current scenario of peptide-based drugs: the key roles of cationic antitumor and antiviral peptides - Mulder, Kelly; Lima, Loiane Alves; Miranda, Vivian; Dias, Simoni C.; Franco, Octavio L. (Frontiers in Microbiology, 2013)
Cationic antimicrobial peptides (AMPs) and host defense peptides (HDPs) show vast potential as peptide-based drugs. Great effort has been made in order to exploit their mechanisms of action, aiming to identify their targets as well as to enhance their activity and bioavailability. In this review, we will focus on both naturally occurring and designed antiviral and antitumor cationic peptides, including those here called promiscuous, in which multiple targets are associated with a single peptide structure. Emphasis will be given to their bio-chemical features, selectivity against extra targets and molecular mechanisms. Peptides which possess antitumor activity against different cancer cell lines will be discussed, as well as peptides which inhibit virus replication, focusing on their applications for human health, animal health and agriculture, and their potential as new therapeutic drugs. Moreover, the development of production and nano-delivery systems for both classes of cationic peptides and perspectives on improving them will be considered.